Leadership of Former Corruption Convicts in Government Analysis of Fiqh Siyasah (Case Study of Constitutional Court Decision Number 03-03/PHPU/DPD-XXII/2024) - Saputra, Edi; Iwan, Iwan (LEGAL BRIEF, 2024)
This study discusses the leadership rights of former corruption convicts in government, especially through the Constitutional Court Decision Number 03-03/PHPU.DPD-XXII/2024, highlighting how constitutional rights and ethics of leadership in government. This study uses a normative legal method to analyze the application of legal norms and collect data through literature studies, including the Constitutional Court Decision Number 03-03/PHPU/DPD-XXII/2024. This paper raises 2 (two) problem formulations, namely: (1) How is the leadership of corruption convicts in government based on the Constitutional Court Decision Number 03-03/PHPU/DPD-XXII/2024 and (2) What is the view of fiqh siyasah on the leadership of former corruption convicts in government. The results of this study indicate that the rights of former convicts to lead in government are recognized based on the Constitutional Court decision, which is a constitutional right that must be recognized and restored. However, this is considered contrary to Islamic principles and leadership ethics, which consider individuals with a history of corruption unfit to lead. From the perspective of siyasah fiqh, the opportunity for former convicts to participate in elections is considered not in accordance with the leadership criteria set by the sharia